Interactive Nature of Foreign Language Teaching - Karamatovna, Ravshanova Nasiba (Researchparks Publishing, 2023)
The article deals with issues related to the principle of interactivity of modern language education in the non-philological specialties. The definition of interactivity as one of the fundamental principles of teaching a foreign language is given, as well as the characteristics of the means, methods and techniques that contribute to the organization of interactive teaching of foreign languages.